Analisis Manajemen Rantai Pasok Pada Perusahaan Cargo dan Courier Service Di Batam - Jessica Fristy Kasih Zebua; Yunisa Oktavia (LPPM Universitas Putera Batam, 2025)
This study discusses the analysis of supply chain management at Cargo dan Courier Service Batam Company, a logistics company based in Batam, Indonesia. The research applies a descri Perusahaanive qualitative method through literature review and company case study. The purpose of this research is to describe the implementation of supply chain management, identify the challenges faced, and analyze the strategies implemented to improve operational efficiency. The results show that PERUSAHAAN Cargo dan Courier Service Batam has adoPerusahaaned information technology-based supply chain management systems, including ERP integration, real-time tracking, and warehouse automation. These implementations successfully reduced delivery delays by up to 40%, improved efficiency by 25%, and enhanced customer satisfaction. However, the company continues to face external challenges such as fluctuating transportation costs, customs regulations, and weather related risks that may affect distribution. In conclusion, the integrated technology-based supply chain management system is a key factor in achieving competitiveness in the logistics industry within the global market.